Sejarah Konflik Muslim Rohingya - Wasalmi Wasalmi (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2023)
The Rohingya are a Muslim population in the Mayu Frontier region, today's Buthidaung and the towns of Maungdaw Arakan (Rakhine), a remote province in the west of the country which includes the entire Naaf River on the border of Bangladesh. Arakan was once an independent kingdom before it was conquered by the Burmese in 1784. This research aims to find out the condition of the Rohingya Muslims, what are the reasons behind the expulsion of the Rohingya Muslims from their own territory and how to solve the problems faced by the Rohingya Muslims.